2015
DOI: 10.1007/s00467-015-3164-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the eNOS G894T gene polymorphism with target organ damage in children with newly diagnosed primary hypertension

Abstract: BackgroundThe endothelial nitric oxide synthase (eNOS) G894T gene polymorphism is associated with the risk of primary hypertension (PH) and vascular complications in adults with PH.MethodsWe explored the associations of the G894T polymorphism with 24-h ambulatory blood pressure, left ventricular mass (LVM), carotid intima media thickness (cIMT), urinary albumin excretion, oxidative stress and inflammatory parameters in 126 children with newly diagnosed PH and in 83 healthy children.ResultsAmong the 126 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
4
0
4
Order By: Relevance
“…It is reported that thiols transform into reversible disulphide structures during oxidative stress and are then reduced back to thiol groups when the oxidative stress is removed. A study by Stoppa-Vaucher and colleagues (2012) investigating teenagers with essential hypertension reported higher disulphide levels indicating increased oxidative stress [ 60 ]. In addition, another study comparing the body mass index of matched controls showed that children with hypertension had a worse antioxidative capability due to considerable glutathione depletion [ 61 ].…”
Section: Clinical Significance Of Oxidative Stress Parameters Associa...mentioning
confidence: 99%
“…It is reported that thiols transform into reversible disulphide structures during oxidative stress and are then reduced back to thiol groups when the oxidative stress is removed. A study by Stoppa-Vaucher and colleagues (2012) investigating teenagers with essential hypertension reported higher disulphide levels indicating increased oxidative stress [ 60 ]. In addition, another study comparing the body mass index of matched controls showed that children with hypertension had a worse antioxidative capability due to considerable glutathione depletion [ 61 ].…”
Section: Clinical Significance Of Oxidative Stress Parameters Associa...mentioning
confidence: 99%
“…Встановлено, що серед пацієнтів із первинною АГ, поєднаною з надмірною масою тіла, суттєво переважає гомозиготний генотип GG (60,3% проти 47,6% в європейській популяції), гомозиготний ТТ виявлено вдвічі рідше, ніж у пацієнтів з АГ в Європі (5,2% проти 10,3%) (табл. 1) [15,16].…”
Section: результати дослідження та їх обговоренняunclassified
“…2). Поліморфний алель Т зустрічається серед обстежених нами пацієнтів з АГ та надмірною масою тіла в 1,3 разу рідше, ніж у пацієнтів з АГ європейської популяції (39,7% проти 52,4%) [15,16].…”
Section: результати дослідження та їх обговоренняunclassified
See 1 more Smart Citation
“…Επίσης, τα δεδομένα μιας μελέτης σε υπερτασικό παιδιατρικό πληθυσμό έδειξαν ότι οι φορείς του αλληλόμορφου Τ του πολυμορφισμού της eNOS είχαν αυξημένες τιμές cIMT συγκριτικά με τους μάρτυρες, υποδηλώνοντας μια προδιάθεση για πρώιμη βλάβη του αρτηριακού τοιχώματος υπό συνθήκες αυξημένης αρτηριακής πίεσης [194]. [147].…”
Section: αγγειολογικές και αιμοδυναμικές μετρήσειςunclassified